Affinity Research Groups in Practice: Apprenticing Students in Research. Issue 3 (17th October 2013) - Villa, Elsa Q.; Kephart, Kerrie; Gates, Ann Q.; Thiry, Heather; Hug, Sarah
Abstract Background The affinity research group (ARG) model is a set of practices built on a cooperative team framework to support the creation and maintenance of dynamic and inclusive research groups in which students learn and apply the knowledge and skills required for research and cooperative work. Using situated learning theory, we conducted a qualitative study of current and former ARG members to understand the potential of the ARG for preparing students for graduate school and professional research careers. Purpose Our study investigated how the ARG model influenced students, particularly those from underrepresented groups, in becoming researchers and practicing computer scientists. Design/Method We employed multiple data collection methods, including individual and focus group interviews and participant observation, to investigate whether this model had lasting effects and sustainability beyond the time students spent in an ARG. Results Using themes emerging from our data analysis, we can explain how students become contributing members of ARGs, group identity and cohesiveness are formed, members learn collaboratively, members participate in larger professional communities, and participants' identities are transformed from student to researcher. Conclusions Findings suggest that the structural and procedural elements of ARGs support students' growth and development as researchers and their gradual socialization into broader computer science research and professional communities through legitimate peripheral participation and immersion in situated practice.